Emerging Methods for Enhancing Pluripotent Stem Cell Expansion - Chan, Sarah W.; Rizwan, Muhammad; Yim, Evelyn K. F. (Frontiers in Cell and Developmental Biology, 2020)
Pluripotent stem cells (PSCs) have great potential to revolutionize the fields of tissue engineering and regenerative medicine as well as stem cell therapeutics. However, the end goal of using PSCs for therapeutic use remains distant due to limitations in current PSC production. Conventional methods for PSC expansion have limited potential to be scaled up to produce the number of cells required for the end-goal of therapeutic use due to xenogenic components, high cost or low efficiency. In this mini review, we explore novel methods and emerging technologies of improving PSC expansion: the use of the two-dimensional mechanobiological strategies of topography and stiffness and the use of three-dimensional (3D) expansion methods including encapsulation, microcarrier-based culture, and suspension culture. Additionally, we discuss the limitations of conventional PSC expansion methods as well as the challenges in implementing non-conventional methods.